Suppression of yolk formation, oviposition and egg quality of locust (Locusta migratoria manilensis) infected by Paranosema locustae - Hu, Yao-Wen; Wang, Shao-Hua; Tang, Ya; Xie, Guo-Qiang; Ding, Yan-Juan; Xu, Qing-Ye; Tang, Bin; Zhang, Long; Wang, Shi-Gui (Frontiers in Immunology, 2022)
Locusta migratoria manilensis is one of the most important agricultural pests in China. The locust has high fecundity and consumes large quantities of food, causing severe damage to diverse crops such as corn, sorghum, and rice. Immunity against pathogens and reproductive success are two important components of individual fitness, and many insects have a trade-off between reproduction and immunity when resources are limited, which may be an important target for pest control. In this study, adult females L. migratoria manilensis were treated with different concentrations (5 × 106 spores/mL or 2 × 107 spores/mL) of the entomopathogenic fungus Paranosema locustae. Effects of input to immunity on reproduction were studied by measuring feeding amount, enzyme activity, vitellogenin (Vg) and vitellogenin receptor (VgR) production, ovary development, and oviposition amount. When infected by P. locustae, feeding rate and phenol oxidase and lysozyme activities increased, mRNA expression of Vg and VgR genes decreased, and yolk deposition was blocked. Weight of ovaries decreased, with significant decreases in egg, length and weight.Thus, locusts used nutritive input required for reproduction to resist invasion by microsporidia. This leads to a decrease in expression of Vg and VgR genes inhibited ovarian development, and greatly decreased total fecundity. P. locustae at 2 × 107 spores/mL had a more obvious inhibitory effect on the ovarian development in migratory locusts. This study provides a detailed trade-off between reproduction and immune input of the female, which provides a reliable basis to find pest targets for biological control from those trade-off processes.